Covid19 and work-life-balance among private-sector employees in India: proposing future human resource strategies - Lakshmi Kanthan, Sindhuja (2022)
The speedy growth of the trade, labour market and transnational interdependence of capital lead to many issues where Work Life Balance (WLB) is one among the issues. Today, WLB plays a significant role in determining the performance of employees in any industry which is majorly prioritized by the employed millennials. In the world history, Covid 19 pandemic is the greatest one. Around 48% of the population of India are bread winners. The most arguable human resource topic during this period is WLB pre (Work from office) and during the phase of Covid 19 pandemic (Work from Home) among private sector employees in India, that perhaps relentlessly change its definition. Private sectors are the most significant in the Indian economy. What is BPOs ( BPOs) contribute 51 percentage of Business Process Out sourcing requirements across the world, one among profitable industries in India. India’s export of private sectors (IT and BPO) is growing. The Private sector contributes a share of profits to India’s GDP which is amounted to about 2.2% in 2018. This shows that employment in India will certainly increase in future. The concept of working from home is the new normal which sets the tone for the research to find the influence of three elements personal life, family and social life and organizational life on Overall WLB pre and during the covid 19 pandemic. The literature confirms that the balance between work and the life is a central issue distressing wellbeing, as personal life, family life and work life are the three most significant elements of any individual’s life in the phase of pre Covid 19 Pandemic – Work from Office and also during Covid 19 Pandemic – Work from Home. Any challenging demands of work can negatively impact these three elements on both the phases. The main findings reveal personal life is affected during the Covid 19 pandemic – work from home, family -social life are affected in the phase of Pre Covid 19 pandemic – Work from Office Organization is affected during the pandemic – Work from home and these determinants can significantly influence overall balance between work and life. On an overall Personal and organizational life are better Pre Covid 19 Pandemic work from office, however amending few changes in the practices can lead to have a better impact on overall work life balance. Few recommendations were made to the organizations based on the findings which will help in mitigating problems such as Workload and stress, lack of work satisfaction, Blurred decision making, lack of support from supervisors, insufficient employee benefits., so that employees of private sectors in India can maintain better work life balance. The research emphasized limitations associated to online survey pre (Work from Office) and during Covid 19 Pandemic (Work from Home) and to propose future human resource strategies.